Modelling of residential land-use, in a joint framework of land-use, transport and economy - Barry Zondag (European Regional Science Association (ERSA), 2002)
An evaluation scheme for transport infrastructure projects, presently adopted by the Dutch government, includes a research challenge to develop a spatial-economic model addressing the indirect impacts of infrastructure measures. Presently several developments in the field of spatial-economic modelling are ongoing in the Netherlands. The Mobilec model is an example of such a development. The Mobilec model is an interregional model, at NUTS3 level, that describes the relationship between productivity, mobility and infrastructure. The current model lacks spatial detail and an adequate modelling of the housing market and labour market. These aspects need to be included to model the location effects. The proposed paper will explore the development of a housing market model, at a spatially detailed level, within the Mobilec framework. The housing market modelling approach should incorporate the context of a strongly regulated housing market in the Netherlands. International state-of-the-art housing market modelling approaches, commonly used in the so-called LUTS models, will be used as starting point of the analysis. In the paper the outline of the residential location model will be presented and some first experiences with a test version of the housing market model in association with Mobilec will be reported.
Keywords: 330